Voltammetric detection of ovalbumin at screen-printed electrodes in combination with immunomagnetic particles - Čadková, Michaela; Korecká, Lucie; Šálek, Petr; Metelka, Radovan; Bílková, Zuzana (Univerzita Pardubice, 2011)
Possibility of determination of ovalbumin as a model protein based on ELISA principle is reported in this contribution. Model system consisted of anti-ovalbumin IgG (primary antibody), ovalbumin and anti-ovalbumin-HRP (secondary antibody). After the addition of substrate (hydrogen peroxide), current decrease induced by its conversion by HRP has been detected by linear sweep voltammetry. Superparamagnetic microspheres were used for covalent immobilization of primary antibodies, which enables better antigen recognition compared to common sorption onto electrode surface.
Keywords: voltammetric detection; biosensor; ovalbumin; magnetic microspheres; screen-printed electrodes; ELISA